Effects of Hurricane Maria in hamlet communities (Serranidae: Hypoplectrus spp.) in Puerto Rico. (December 2019) - Meléndez-Vazquez, Fernando; Olmeda-Saldaña, Manuel; Cruz, Juan; Arcila, Dahiana; Betancur, Ricardo
Highlights: Hypoplectrus communities suffered a decline in composition from 2000–2017. Increase in diversity and abundance was observed following Hurricane Maria. Hypoplectrus randallorum was recorded in the reserve for the first time in 2018. Natural disturbances can act as a driver for fish community restoration. Abstract: Hamlets ( Hypoplectrus spp.) are hermaphroditic, carnivorous, and highly territorial fishes in the family Serranidae that are endemic to the Western Atlantic. We studied 10 reefs located in the La Parguera Natural Reserve in Puerto Rico and report differences in hamlet communities after the passage of Hurricane Maria. Our results were compared to surveys conducted in the years 2000 and 2017, before the reefs were hit by Hurricane Maria in 2017. Non-metric multidimensional analyses revealed a "boomerang pattern" in species composition and abundance, with high diversity in 2000, low diversity in 2017, and a subsequent return to high diversity levels in 2018. By and large, the study reveals a positive effect on the diversity of hamlet communities in the aftermath of Hurricane Maria. The reemergence of diversity patterns, including the recording of previously unobserved species in the study site serves as indicator of the underlying and often underestimated benefits of major disturbance events.